Peran Guru sebagai Motivator Pembelajaran pada Masa Pandemi Covid-19 di Sekolah Dasar - Tripenita, Dian; Mustika, Dea (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to describe the role of teachers in motivating elementary school student learning during the COVID-19 pandemic. This research design uses a qualitative descriptive approach. The research was conducted at SDN 151 Pekanbaru. The data sources in this study involved two fourth-grade teachers, namely a class IV A teacher and a class IV teacher as well as two grade IV A students and two grade IV B students. Data collection techniques in this study used observation, interviews, and document review. Data analysis used the Milles and Huberman model with the stages of data reduction, data presentation, and drawing conclusions. The results showed that there were nine roles of teachers in providing motivation to students, including giving motivation, giving praise, giving gifts, giving assignments, using various teaching methods, using learning media, giving grades, and giving punishments. From the results of the research conducted, it can be said that teachers at SDN 151 Pekanbaru have tried to use it in motivating student learning during the pandemic covid-19.